The aid relationship in the of teaching and learning - Ana Lucía Noreña Peña; Noemí Alcaraz Moreno; Genoveva Amador Fierros; Francisco Javier Ramos Sánchez (Universidad de Alicante, 2013)
Through a retrospective analysis on the educational characteristics of nursing education, there is a reflection on the type of learning promoted from an ad hoc university teaching practice and how it has influenced nursing education. It outlines some perspectives about change in mentality that has been occurring in nursing schools, by promoting new forms of teaching and learning, from which value the role of the student in order to achieve their full development. It proposes the construction of facilitated learning through the aid relationship, ethical and creative design of the constructive process of professional knowledge.